The Effect of Linguistic Tools used in Daud Kamal’s Poem Stone Bridge: A Stylistic Study - Gulranga Haider,; Muhammad Ramzan, (Al-Qanṭara, 2023)
The research embodies the analysis of Daud Kamal’s poem “Stone Bridge” through stylistics. The study mainly analyzes the poem through four levels of stylistics i.e., Phonological, Graphological, Morphological and Lexico-syntactic. The purpose of the current research is to make the meaning objective, and to explore the stylistic devices which are used in the poem understudy. Every poet has his/her own style through which the poet is known. Daud Kamal has his own unique style which places him above all the Pakistani poets who write poetry in English. He uses different tools and linguistic devices in his poetry which made his poetry difficult to a great extent for the budding readers. Analyzing his poetry from the perspective of stylistics will prove fruitful for learners, researchers and teachers alike. The researchers have made the meaning explicit for the readers by exploring the stylistic devices employed by the poet.